Cosmetic Surgery - Tang, Yueh-Bih (IntechOpen, 2021)
This edited volume, Cosmetic Surgery, is a collection of reviewed and relevant research chapters that offer a comprehensive overview of recent developments in the field of medicine. The book comprises single chapters authored by various researchers and edited by an expert active in the cosmetic surgery research area. All chapters are complete in themselves but united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts by international authors on cosmetic surgery, and open new possible research paths for further novel developments.